A directed assembled anisotropic nanocrystalline composite rare earth permanent magnet and a preparation method thereof

Through directional assembly and hot pressing and thermal deformation methods, the problem of insufficient magnetic properties and use temperature of rare earth permanent magnet materials is solved, and the magnetic properties and magnetic anisotropy are improved, thereby avoiding element diffusion and deterioration in comparison.

CN114628101BActive Publication Date: 2025-04-22BEIJING UNIV OF TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202210291872.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-03-22
Publication Date
2025-04-22
Estimated Expiration
2042-03-22

AI Technical Summary

Technical Problem

The existing rare earth permanent magnet materials have shortcomings in magnetic properties and use temperature, and traditional sintering methods are difficult to avoid elemental interdiffusion and deterioration in comparison, and hot pressing and thermal deformation methods are also difficult to effectively improve magnetic properties.

Method used

Directional assembly combined with hot pressing and thermal deformation method is adopted to improve magnetic performance and magnetic anisotropy by controlling the relative distribution of the elementary phases and using magnetic static interaction and exchange coupling.

Benefits of technology

Through directional assembly and hot pressing and thermal deformation, the magnetic properties and magnetic anisotropy of rare earth permanent magnet materials are significantly improved, and the problems of element diffusion and uneven deformation of the two phases are reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114628101B_ABST
    Figure CN114628101B_ABST
Patent Text Reader

Abstract

A directionally assembled anisotropic nanocrystalline composite rare earth permanent magnet and a preparation method thereof belong to the technical field of rare earth permanent magnet material preparation. The magnet prepared by the method is formed by directional assembly of two primitives with high saturation magnetization intensity and high magnetic anisotropy layer by layer. The preparation method comprises: preparing nanocrystalline / amorphous rare earth permanent magnet powder as an assembly primitive; directionally assembling and pressing into a thermally deformed precursor; thermally deforming the precursor to obtain a directionally assembled anisotropic nanocrystalline composite rare earth permanent magnet. The directionally assembled nanocrystalline composite rare earth permanent magnet prepared by the present invention can achieve a significant improvement in magnetic properties by coordinating long-range static magnetointeraction and short-range exchange coupling.
Need to check novelty before this filing date? Find Prior Art

Description

Technical field:

[0001] The invention relates to a directionally assembled anisotropic nanocrystalline composite rare earth permanent magnet and a preparation method thereof, belonging to the technical field of rare earth permanent magnet material preparation. Background technology:

[0002] As basic functional materials, rare earth permanent magnet materials are widely used in various fields such as automobile industry, industrial motors, energy-saving home appliances and consumer electronics, clean energy, aerospace, medical and health care, etc. Since their development, cobalt-based rare earth permanent magnets and iron-based rare earth permanent magnets have been widely used. However, due to the inherent magnetic properties, magnets with a single permanent magnetic phase can no longer meet the performance requirements of permanent magnetic materials in rapidly developing application fields, such as the low magnetic energy product of samarium cobalt permanent magnets and the low operating temperature and heavy reliance on scarce heavy rare earth resources of neodymium iron boron permanent magnets. In this context, the idea of ​​composite magnets has become one of the effective ways to prepare high comprehensive magnetic properties. It is difficult to avoid serious element interdiffusion and deterioration of magnetic properties when preparing composite magnets using traditional sintering methods. The hot pressing and hot deformation method for preparing anisotropic nanocrystalline permanent magnet materials has become an ideal choice for preparing composite permanent magnet materials because it can achieve density at a lower temperature and induce magnetic anisotropy. However, due to factors such as inevitable element diffusion, uneven deformation of the two phases, and difficult-to-control magnetic interactions, the magnetic properties of composite magnets are still poor, and new ideas and technologies are urgently needed to improve the magnetic properties of composite magnets. The present invention adopts a method of directional assembly combined with hot pressing and hot deformation, and effectively utilizes static magnetointeraction and exchange coupling to improve magnetic properties and magnetic anisotropy by controlling the relative distribution of elementary phases. Summary of the invention:

[0003] The invention provides a directionally assembled anisotropic nanocrystalline composite rare earth permanent magnet and a preparation method thereof. The method can achieve a significant improvement in magnetic properties and magnetic anisotropy through a layered directional assembly design.

[0004] Specifically, the present invention provides the following technical solutions:

[0005] A directional assembled anisotropic nanocrystalline composite rare earth permanent magnet and a preparation method thereof, comprising the following steps:

[0006] (1) preparing nanocrystalline / amorphous rare earth permanent magnetic powder as assembly unit;

[0007] (2) Directed assembly and pressing into a thermal deformation precursor, and then thermal deformation to obtain a directed assembled anisotropic nanocrystalline composite rare earth permanent magnet.

[0008] The step (1) of assembling the primitives of the present invention comprises at least primitive 1 and primitive 2, wherein primitive 1 is one or more rare earth permanent magnet compounds with high magnetic anisotropy, such as R 1 Co5-x TM x , where R 1 is one or more of Sm, Pr, La, Ce, and Y, TM is one or more of Ni, Fe, Mn, Cr, Al, Sn, Ga, Ti, Zn, Zr, Mo, Ag, Cu, B, Nb, and Hf, 0≤x≤1; the second unit is one or more rare earth permanent magnet compounds with high saturation magnetization intensity, such as R 2 2Fe 14 B(R 2 is one or more of the rare earth elements such as Nd, Pr, La, Ce, Ho, Dy, Tb, Y, etc.) series (including rare earth-rich phase and R 2 2Fe 14 Alloys composed of B, R 2 2Fe 14 B and soft magnetic phase composed of hard and soft nanocomposite alloy) and / or R 1 -Co-based soft and hard nanocomposite alloy, R 1 It is one or more of Sm, Pr, La, Ce, and Y, and TM is one or more of Ni, Fe, Mn, Cr, Al, Sn, Ga, Ti, Zn, Zr, Mo, Ag, Cu, B, Nb, and Hf.

[0009] The nanocrystalline / amorphous magnetic powder used as the assembly unit of the present invention is prepared by batching, vacuum induction melting, melt rapid quenching and / or high-energy ball milling.

[0010] The formula R of the present invention 1 Co 5-x TM x Alloy, actual ratio R 1 Theoretical R 1 1.03 to 1.10 times the consumption, the actual R after consumption 1 The amount exceeds the theoretical rare earth R 1 Quantity is the key to regulating the thermal deformation ability of the element.

[0011] The two selected elements of the present invention can achieve similar thermal deformation capabilities by adjusting the rare earth content, thereby achieving coupling of deformation conditions.

[0012] The directional assembly in step (2) of the present invention includes two methods: one is to cold-press the two nanocrystalline / amorphous elementary magnetic powders into thin sheets respectively, and then lay them out alternately layer by layer, and then perform hot pressing and thermal deformation; the other is to hot-press the two nanocrystalline / amorphous elementary magnetic powders into blocks respectively, and then cut them into thin sheets, and then lay them out alternately layer by layer, and then perform thermal deformation.

[0013] The hot pressing process of the present invention is: temperature 400-700°C, pressure 200-1000MPa; the thermal deformation process is: deformation temperature 600-800°C, pressure 50-500MPa, deformation amount 70-90%.

[0014] The deformation process of the present invention is carried out at a high deformation rate (more than 0.01 mm / s) and the deformation time is shortened to avoid diffusion between the two elements.

[0015] In the hot pressing and hot deformation process of the present invention, the pressing direction is the same as the assembly direction (layer thickness direction). After hot deformation, the crystallographic orientation texture obtained by the magnet is the same as the assembly direction (layer thickness direction).

[0016] The thickness of the two primitives of the deformed product of the present invention is optimally between 50-500 μm, and the two primitives are arranged alternately, with no specific requirement on the number of layers. The number of assembly layers and the thickness of the precursor should be designed in combination with the size of the final product.

[0017] Beneficial effects of the present invention:

[0018] Directed assembly combined with hot pressing and hot deformation methods can obtain a directed distribution of primitives, thereby effectively utilizing magnetic interactions and improving the magnetic properties and magnetic anisotropy of the magnet. Specifically, the primitives are assembled layer by layer in the pressure direction, and after deformation, the easy axis direction of the magnet is the same as the assembly direction (pressure direction). This structure can effectively utilize long-range static magnetointeractions, combined with short-range exchange interactions near the interface to achieve good coupling between primitives. This directed distribution of primitive combination can also effectively utilize the directional differences in the demagnetization field and enhance the effective magnetic anisotropy. On the other hand, the layered directed assembly method can also reduce the contact interface of the primitives, reduce the diffusion of elements between the primitives, and improve the magnetic properties. Description of the drawings:

[0019] Figure 1 The process roadmap for the preparation of nanocrystalline composite permanent magnets with directed assembly.

[0020] Figure 2 (a)-(c) are backscattered electron images taken by scanning electron microscope of Example 1, Example 2 and Comparative Example respectively. Specific implementation method:

[0021] The following examples are used to illustrate the present invention, but are not intended to limit the scope of the present invention. If no specific techniques or conditions are specified in the examples, the techniques or conditions described in the literature in the art or the product instructions are used.

[0022] In the following examples, the instruments used without indicating the manufacturer are all conventional products that can be purchased through regular channels. The methods described are conventional methods unless otherwise specified, and the raw materials described can be obtained from public commercial channels unless otherwise specified.

[0023] Example 1

[0024] 1) According to the chemical formula Sm 0.6 Pr 0.4 Co5 and SmCo5 were batched separately, and the actual amount of Sm and Pr in the batching process was 1.05 times the theoretical Sm and Pr consumption. The alloy raw materials were melted in a PZGF-40 medium frequency vacuum induction melting furnace under argon atmosphere, and the heating power was increased from 5kW to 8kW, 10kW, and 13kW in sequence. The corresponding residence time was 5min, 3min, 3min, and 2min, respectively. A water-cooled copper mold was used during casting to obtain the corresponding alloy ingots with a thickness of 10mm.

[0025] 3) Sm 0.6 Pr 0.4 Co5 alloy and SmCo5 alloy were melt-quenched at a roller speed of 25 m / s in an argon atmosphere to obtain Sm 0.6 Pr 0.4 Co5 and SmCo5 rapid quenching strips.

[0026] 4) Sm 0.6 Pr 0.4 The Co5 quenched strip was placed in a stainless steel tank, and stainless steel balls were used as ball milling media. The diameter of the stainless steel balls was 4-12 mm, the ball-to-material ratio was 15:1, and the rotation speed was 600 r / min. It was ball milled in a GN-2 high-energy ball mill for 4 hours under an argon atmosphere to obtain amorphous permanent magnetic powder as element one.

[0027] 5) The SmCo5 quenching strip and 20wt.% Fe powder are mixed evenly and put into a stainless steel tank. Stainless steel balls are used as ball milling media. The diameter of the stainless steel balls is 4-12mm, the ball-to-material ratio is 15:1, the rotation speed is 600r / min, and the mixture is ball milled in a GN-2 high-energy ball mill for 4 hours under an argon atmosphere to obtain SmCo5 / α-Fe nanocrystalline / amorphous permanent magnet powder as the second unit.

[0028] 6) The two elementary magnetic powders of steps 4) and 5) were cold pressed into thin sheets with a diameter of 10 mm and a thickness of 1 mm, respectively, and then the compacted thin sheets were assembled layer by layer, and then loaded into a mold for hot pressing under a vacuum state (less than 10 Pa). The hot pressing process temperature was 600°C, the pressure was 500 MPa, and the holding time was 5 min to prepare a hot deformation precursor.

[0029] 6) The hot precursor of step 6) is loaded into a mold and subjected to thermal deformation under vacuum (less than 10Pa), the temperature is raised to 700°C, the pressure is gradually applied to 300MPa, the average deformation rate is 0.015mm / s, and a directional assembled nanocrystalline composite rare earth permanent magnet with a deformation amount of 70% is obtained.

[0030] Example 2

[0031] 1) According to the chemical formula Sm 0.6 Pr 0.4 Co5 and SmCo5 were batched separately, and the actual amount of Sm and Pr in the batching process was 1.05 times the theoretical Sm and Pr consumption. The alloy raw materials were melted in a PZGF-40 medium frequency vacuum induction melting furnace under argon atmosphere, and the heating power was increased from 5kW to 8kW, 10kW, and 13kW in sequence. The corresponding residence time was 5min, 3min, 3min, and 2min, respectively. A water-cooled copper mold was used during casting to obtain the corresponding alloy ingots with a thickness of 10mm.

[0032] 3) Sm 0.6 Pr 0.4 Co5 alloy and SmCo5 alloy were melt-quenched at a roller speed of 25 m / s in an argon atmosphere to obtain Sm 0.6 Pr 0.4 Co5 and SmCo5 rapid quenching strips.

[0033] 4) Sm 0.6 Pr 0.4 The Co5 quenched strip was placed in a stainless steel tank, and stainless steel balls were used as ball milling media. The diameter of the stainless steel balls was 4-12 mm, the ball-to-material ratio was 15:1, and the rotation speed was 600 r / min. It was ball milled in a GN-2 high-energy ball mill for 4 hours under an argon atmosphere to obtain amorphous permanent magnetic powder as element one.

[0034] 5) The SmCo5 quenching strip and 20wt.% Fe powder are mixed evenly and put into a stainless steel tank. Stainless steel balls are used as ball milling media. The diameter of the stainless steel balls is 4-12mm, the ball-to-material ratio is 15:1, the rotation speed is 600r / min, and the mixture is ball milled in a GN-2 high-energy ball mill for 4 hours under an argon atmosphere to obtain SmCo5 / α-Fe nanocrystalline / amorphous permanent magnet powder as the second unit.

[0035] 6) The elementary magnetic powder of step 4) is placed in a mold and hot pressed under vacuum (less than 10 Pa) at a temperature of 600° C., a pressure of 500 MPa, and a holding time of 5 min to prepare Sm 0.6 Pr 0.4 Co5 (element one) hot pressed magnet.

[0036] 7) The elementary two magnetic powder of step 5) is loaded into a mold and hot pressed under vacuum (less than 10Pa) at a temperature of 500°C and a pressure of 500MPa for a holding time of 5min to prepare a SmCo5 / α-Fe (element two) hot pressed magnet.

[0037] 8) Cutting the hot pressed magnets of step 6) and step 7) into 1 mm thick sheets respectively, and then assembling the two primitives layer by layer, and then molding to obtain a hot deformed precursor;

[0038] 9) The hot precursor of step 8) is thermally deformed in a vacuum state (less than 10Pa), the temperature is raised to 700°C, the pressure is gradually applied to 300MPa, the average deformation rate is 0.015mm / s, and a directional assembled nanocrystalline composite rare earth permanent magnet with a deformation amount of 70% is obtained.

[0039] Example 3

[0040] 1) According to the chemical formula SmCo 4.89 Sn 0.11 and SmCo5 were separately batched, and the actual amount of Sm in the batching process was 1.05 times the theoretical Sm consumption. The alloy raw materials were melted in a PZGF-40 medium frequency vacuum induction melting furnace under argon atmosphere, and the heating power was increased from 5kW to 8kW, 10kW, and 13kW in sequence. The corresponding residence time was 5min, 3min, 3min, and 2min, respectively. A water-cooled copper mold was used for casting, and the corresponding alloy ingots with a thickness of 10mm were obtained.

[0041] 3) SmCo 4.89 Sn 0.11 The alloy and SmCo5 alloy were melt-quenched in an argon atmosphere at a roller speed of 25 m / s to obtain SmCo 4.89 Sn 0.11 And SmCo5 rapid quenching belt.

[0042] 4) SmCo 4.89 Sn 0.11 The quenched strip was placed in a stainless steel tank, and stainless steel balls were used as ball milling media. The diameter of the stainless steel balls was 4-12 mm, the ball-to-material ratio was 15:1, and the rotation speed was 600 r / min. It was ball milled in a GN-2 high-energy ball mill for 4 hours under an argon atmosphere to obtain amorphous permanent magnetic powder as the first element.

[0043] 5) The SmCo5 quenching strip and 20wt.% Fe powder are mixed evenly and put into a stainless steel tank. Stainless steel balls are used as ball milling media. The diameter of the stainless steel balls is 4-12mm, the ball-to-material ratio is 15:1, the rotation speed is 600r / min, and the mixture is ball milled in a GN-2 high-energy ball mill for 4 hours under an argon atmosphere to obtain SmCo5 / α-Fe nanocrystalline / amorphous permanent magnet powder as the second unit.

[0044] 6) The elementary magnetic powder of step 4) is placed in a mold and hot pressed under vacuum (less than 10 Pa) at a temperature of 600° C., a pressure of 500 MPa, and a holding time of 5 min to prepare SmCo 4.89 Sn 0.11 (Element 1) Hot pressed magnet.

[0045] 7) The elementary two magnetic powder of step 5) is loaded into a mold and hot pressed under vacuum (less than 10Pa) at a temperature of 500°C and a pressure of 500MPa for a holding time of 5min to prepare a SmCo5 / α-Fe (element two) hot pressed magnet.

[0046] 8) Cutting the hot pressed magnets of step 6) and step 7) into 1 mm thick sheets respectively, and then assembling the two primitives layer by layer, and then molding to obtain a hot deformed precursor;

[0047] 9) The hot precursor of step 8) is thermally deformed in a vacuum state (less than 10Pa), the temperature is raised to 700°C, the pressure is gradually applied to 300MPa, the average deformation rate is 0.015mm / s, and a directional assembled nanocrystalline composite rare earth permanent magnet with a deformation amount of 70% is obtained.

[0048] Example 4

[0049] 1) According to the chemical formula Pr2Fe 14 B and (Sm 0.6 Pr 0.4 )Co5 were separately batched, and the actual amount of Sm and Pr in the batching process was 1.05 times the theoretical Sm and Pr consumption. The alloy raw materials were melted in a PZGF-40 medium frequency vacuum induction melting furnace under argon atmosphere, and the heating power was increased from 5kW to 8kW, 10kW, and 13kW in sequence. The corresponding residence time was 5min, 3min, 3min, and 2min, respectively. A water-cooled copper mold was used during casting to obtain the corresponding alloy ingots with a thickness of 10mm.

[0050] 3) Sm 0.6 Pr 0.4 Co5 alloy and Pr2Fe 14 The B alloy was melt-quenched in an argon atmosphere at a roller speed of 25 m / s to obtain Sm 0.6 Pr 0.4 Co5 and Pr2Fe 14 B rapid quenching belt, in which Pr2Fe 14 B The rapidly quenched strip is directly used as element one.

[0051] 4) Sm 0.6 Pr 0.4The Co5 quenched strip was placed in a stainless steel tank, and stainless steel balls were used as ball milling media. The diameter of the stainless steel balls was 4-12 mm, the ball-to-material ratio was 15:1, and the rotation speed was 600 r / min. It was ball milled in a GN-2 high-energy ball mill for 4 hours under an argon atmosphere to obtain amorphous permanent magnetic powder as element two.

[0052] 5) The elementary magnetic powder of step 4) is placed in a mold and hot pressed under vacuum (less than 10 Pa) at a temperature of 600° C. and a pressure of 500 MPa for a holding time of 5 min to prepare Sm 0.6 Pr 0.4 Co5 (element II) hot pressed magnet.

[0053] 6) The elementary second magnetic powder of step 3) is placed in a mold and hot pressed under vacuum (less than 10Pa) at a temperature of 500°C, a pressure of 500MPa, and a holding time of 5min to prepare Pr2Fe 14 B (element one) hot pressed magnet.

[0054] 7) Cut the hot pressed magnets of step 5) and step 6) into 1 mm thick sheets respectively, and then assemble the two primitives layer by layer, and then mold to obtain a hot deformed precursor;

[0055] 8) The hot precursor of step 7) is thermally deformed under vacuum (less than 10Pa), the temperature is raised to 700°C, the pressure is gradually applied to 200MPa, the average deformation rate is 0.015mm / s, and a directional assembled nanocrystalline composite rare earth permanent magnet with a deformation amount of 70% is obtained.

[0056] Comparative Example

[0057] 1) According to the chemical formula Sm 0.6 Pr 0.4 Co5 and SmCo5 were batched separately, and the actual amount of Sm and Pr in the batching process was 1.05 times the theoretical Sm and Pr consumption. The alloy raw materials were melted in a PZGF-40 medium frequency vacuum induction melting furnace under argon atmosphere, and the heating power was increased from 5kW to 8kW, 10kW, and 13kW in sequence. The corresponding residence time was 5min, 3min, 3min, and 2min, respectively. A water-cooled copper mold was used during casting to obtain the corresponding alloy ingots with a thickness of 10mm.

[0058] 3) Sm 0.6 Pr 0.4 Co5 alloy and SmCo5 alloy were melt-quenched at a roller speed of 25 m / s in an argon atmosphere to obtain Sm 0.6 Pr 0.4 Co5 and SmCo5 rapid quenching strips.

[0059] 4) Sm0.6 Pr 0.4 The Co5 quenched strip was placed in a stainless steel tank, and stainless steel balls were used as ball milling media. The diameter of the stainless steel balls was 4-12 mm, the ball-to-material ratio was 15:1, and the rotation speed was 600 r / min. It was ball milled in a GN-2 high-energy ball mill for 4 hours under an argon atmosphere to obtain amorphous permanent magnetic powder as element one.

[0060] 5) The SmCo5 quenching strip and 20wt.% Fe powder are mixed evenly and put into a stainless steel tank. Stainless steel balls are used as ball milling media. The diameter of the stainless steel balls is 4-12mm, the ball-to-material ratio is 15:1, the rotation speed is 600r / min, and the mixture is ball milled in a GN-2 high-energy ball mill for 4 hours under an argon atmosphere to obtain SmCo5 / α-Fe nanocrystalline / amorphous permanent magnet powder as the second unit.

[0061] 6) The magnetic powders of step 4) and 5) are mixed uniformly in a mass ratio of 1:1, loaded into a mold, and hot pressed under vacuum (less than 10 Pa), with a hot pressing process temperature of 550° C., a pressure of 500 MPa, and a holding time of 5 min to prepare a thermal deformation precursor;

[0062] 6) The hot precursor of step 5) is loaded into a mold and subjected to thermal deformation under vacuum (less than 10Pa), the temperature is raised to 650°C, the pressure is gradually applied to 300MPa, the average deformation rate is 0.015mm / s, and a directional assembled nanocrystalline composite rare earth permanent magnet with a deformation amount of 70% is obtained.

[0063] Magnetic properties test:

[0064] The nanocrystalline composite rare earth permanent magnets prepared in Examples 1-4 and the comparative examples were subjected to magnetic property testing, and the test data are shown in Table 1. Comparison between Example 1 and the comparative example shows that the magnetic properties of the magnet are significantly improved after the directional assembly deformation of the magnetic powder pressed tablets, which is manifested in the simultaneous improvement of the residual magnetism Mr, the coercive force Hci and the maximum magnetic energy product. Comparison between Example 2 and the comparative example shows that the magnetic properties of the magnet are significantly improved after the directional assembly deformation of the elementary hot-pressed magnet slices. On the other hand, the parameter obtained by the residual magnetism tested along the difficulty axis, [Mr(easy)-Mr(difficult)] / Mr(easy)*100%, can characterize the magnetic anisotropy of the magnet. It can be found that the directional assembly hot pressing and hot deformation method described in the present invention can effectively improve the magnetic anisotropy of the magnet. It can be found that the superposition of magnetic properties and magnetic anisotropy improvement of elementary hot-pressed magnet slices is the best.

[0065] Table 1

[0066]

[0067] Although the present invention has been described in detail above by general description, specific implementation methods and experiments, it is obvious to those skilled in the art that some modifications or improvements can be made to the present invention. Therefore, these modifications or improvements made without departing from the spirit of the present invention all belong to the scope of protection claimed by the present invention.

Claims

1. A method for preparing a directional assembled anisotropic nanocrystalline composite rare earth permanent magnet, characterized in that: The following steps are involved: (1) preparing nanocrystalline / amorphous rare earth permanent magnetic powder as assembly unit; (2) Directed assembly and pressing into a thermally deformed precursor, and then thermally deforming to obtain a directed assembled anisotropic nanocrystalline composite rare earth permanent magnet; Step (1) assembling the primitives includes at least primitive one and primitive two, wherein primitive one is one or more rare earth permanent magnet compounds with high magnetic anisotropy, and primitive two is one or more rare earth permanent magnet compounds with high saturation magnetization intensity; The thermal deformation process is as follows: during the deformation process, the deformation rate should be high, exceeding 0.01 mm / s, and the deformation time should be shortened to avoid diffusion between the two primitives; The first primitive is R 1 Co 5-x TM x , where R 1 is one or more of Sm, Pr, La, Ce, and Y, TM is one or more of Ni, Fe, Mn, Cr, Al, Sn, Ga, Ti, Zn, Zr, Mo, Ag, Cu, B, Nb, and Hf, 0≤x≤1; Primitive 2 uses R 2 2Fe 14 B series and / or R 1 -Co-based soft and hard nanocomposite alloy, in which R 2 2Fe 14 Series B is selected from rare earth-rich phase and R 2 2Fe 14 Alloys composed of B, R 2 2Fe 14 Any one or more of the soft and hard nanocomposite alloys composed of B and soft magnetic phase; R 2 is one or more of the rare earth elements Nd, Pr, La, Ce, Ho, Dy, Tb, and Y; the R 1 -Co-based soft and hard nanocomposite alloy is SmCo5 / α-Fe nanocrystalline / amorphous permanent magnet powder; R 1 Co 5-x TM x Alloy, actual ratio R 1 Theoretical R 1 1.03 to 1.10 times the consumption, the actual R after consumption 1 The amount exceeds the theoretical rare earth R 1 The quantity is the key to regulating the thermal deformation ability of the primitive; Step (2) directional assembly includes two methods: one is to cold press the two nanocrystalline / amorphous elementary magnetic powders into thin sheets respectively, and then lay them out alternately layer by layer, and then perform hot pressing and thermal deformation; the other is to hot press the two nanocrystalline / amorphous elementary magnetic powders into blocks respectively, and then cut them into thin sheets, and then lay them out alternately layer by layer, and then perform thermal deformation.

2. The method for preparing a directional assembled anisotropic nanocrystalline composite rare earth permanent magnet according to claim 1, characterized in that: The nanocrystalline / amorphous magnetic powder as the assembly unit is prepared by batching, vacuum induction melting, melt rapid quenching and / or high-energy ball milling.

3. The method for preparing a directional assembled anisotropic nanocrystalline composite rare earth permanent magnet according to claim 1, characterized in that: The two elements achieve similar thermal deformation capabilities by adjusting the rare earth content, thus achieving coupling of deformation conditions.

4. The method for preparing a directional assembled anisotropic nanocrystalline composite rare earth permanent magnet according to claim 1, characterized in that: The thermal deformation precursor pressing process is: temperature 400-700°C, pressure 200-1000MPa; the thermal deformation process is: deformation temperature 600-800°C, pressure 50-500MPa, deformation amount 70-90%.

5. The method for preparing a directional assembled anisotropic nanocrystalline composite rare earth permanent magnet according to claim 1, characterized in that: The hot pressing process is as follows: during the hot pressing and thermal deformation process, the pressing direction is the same as the assembly direction; after the thermal deformation, the crystallographic orientation texture obtained by the magnet is the same as the assembly direction.

6. The method for preparing a directional assembled anisotropic nanocrystalline composite rare earth permanent magnet according to claim 1, characterized in that: The thickness of the two elements of the deformed product is 50-500 μm.

Citation Information

Patent Citations

  • NdFeB / SmCo5 multi-layer composite rare earth permanent magnet and SPS hot-pressing preparation method

    CN105006326A

  • Magnetic phase coupling in composite permanent magnet

    CN107768065A

  • Rare earth permanent magnet composite magnet having multi-plate laminated structure and method of manufacturing same

    CN110323030A